2021
DOI: 10.1093/nc/niab036
|View full text |Cite
|
Sign up to set email alerts
|

Apical amplification—a cellular mechanism of conscious perception?

Abstract: We present a theoretical view of the cellular foundations for network-level processes involved in producing our conscious experience. Inputs to apical synapses in layer 1 of a large subset of neocortical cells are summed at an integration zone near the top of their apical trunk. These inputs come from diverse sources and provide a context within which the transmission of information abstracted from sensory input to their basal and perisomatic synapses can be amplified when relevant. We argue that apical amplif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 181 publications
4
20
0
Order By: Relevance
“…Our finding of larger task-related modulations in the outer layers in FFA (Figure 2, 3) is consistent with two theories: that of apical dendritic amplification 39 in which an already firing neuronal population receives further amplification from higher level areas to apical dendrites; and with the notion of the FFA as an intermediate stage of processing 14,40 . This effect of amplified dendritic activity has been associated with conscious perception, increasing the flexibility of neural coding by rendering it sensitive to context 41 . It has further been suggested that this mechanism of apical amplification contributes to holistic integration of information 41 , a crucial process in face perception 42 .…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of larger task-related modulations in the outer layers in FFA (Figure 2, 3) is consistent with two theories: that of apical dendritic amplification 39 in which an already firing neuronal population receives further amplification from higher level areas to apical dendrites; and with the notion of the FFA as an intermediate stage of processing 14,40 . This effect of amplified dendritic activity has been associated with conscious perception, increasing the flexibility of neural coding by rendering it sensitive to context 41 . It has further been suggested that this mechanism of apical amplification contributes to holistic integration of information 41 , a crucial process in face perception 42 .…”
Section: Mainmentioning
confidence: 99%
“…This effect of amplified dendritic activity has been associated with conscious perception, increasing the flexibility of neural coding by rendering it sensitive to context 41 . It has further been suggested that this mechanism of apical amplification contributes to holistic integration of information 41 , a crucial process in face perception 42 . Accordingly, the FFA may be receiving feedback, in the outer layers, from a higher level face processing region, such as the anterior inferior temporal cortex, which appears to be highly sensitive to the perceived faceness of stimuli 14 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical and empirical work suggests the mechanism of "apical amplification" [95] or "dendritic integration" [96] to be at the core of conscious processing. According to these views, only stimuli that are prioritized by contextual information reach the status of being consciously perceived.…”
Section: Relevance For Cognition and Behaviormentioning
confidence: 99%
“…Such experiments have led to fundamental insight into the large-scale, network-level dynamics of conscious perception. However, despite recent experiments in animal models [4,5] and associated theoretical proposals [6][7][8] , we still lack basic understanding of the cellular-and circuit-level brain dynamics that support conscious perception, particularly across species and sensory modalities. This is likely due to inherent limitations in each neuroimaging method that hinder cellular-and circuit-level interpretation.…”
Section: Introductionmentioning
confidence: 99%